Synthesis and Potentiometric Study of Atenolol Selective Electrodes and Their Use in Determining Some Drugs Issue: - Al-Bayti, Yehya K (Al-Nahrain Journal of Science, 2013)
Atenolol ion selective electrodes were constructed. This construction was based on drug complex formation with phosphomolybdic acid as ionophor and plasticizer, Di-butylphthalate (DBPH), Tri-butylphosphate (TBP), O-nitrophenyloctylether (ONPOE) and Di-octyl phthalate (DOP) in PVC matrix membrane.The matrix membrane was formed by mixing an appropriate plasticizer and drug complex with poly(vinyl chloride) PVC. The properties of following electrodes were studied, concentration range, slope, detection limit, response time, life time, pH effect and selectivity. The results showed that membranes (At-PMA+DBPH) and (At-PMA+ONPOE) gave a linear range from 1× 10−5 to 1× 10−1 and 5× 10−6 to 1× 10−2 respectively, with slopes of (55.6 and 40.5) mV/decade, correlation coefficients are 0.9996 and 0.9984, the detection limit was (8.5× 10−6 and 3.5× 10−5) M, and the response time for 10−3 M were (15 and 25) second respectively.The proposed electrodes were successfully applied to the determination of atenolol in a pharmaceutical preparation and gave a good accuracy